Five-membered random copolymer, preparation method thereof, filtrate reducer and water-based drilling fluid
By using five-member random copolymer as filter reduction agent, the problems of viscosity loss and rheology deterioration of existing drilling fluid filter reduction agents under high temperature and high salt conditions are solved, and efficient application in deep formation oil and gas mining is achieved.
Patent Information
- Application Number
- CN202311139521.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-05
AI Technical Summary
The existing drilling fluid filter reduction agent exhibits viscosity loss, poor rheology, easy decomposition and pollution under high temperature and high salt conditions, resulting in complex underground conditions and limiting its practical application.
A five-membered random copolymer is used as a filter reduction agent. The copolymer is formed by free radical copolymerization of 2-acrylamide-2methyl-1-propane sulfonic acid, N-enylamide, dimethyldiallyl ammonium chloride, N-vinyl caprolactam and alkenyl heterocyclic compounds, and has sulfonic acid groups, quaternary ammonium salt cation groups and heterocyclic groups, which improves its resistance to high temperature, salt resistance and bentonite dispersion stability.
As a filter reduction agent, the five-member random copolymer exhibits a lower filtration loss under high temperature and high salt conditions, which improves the hydration dispersion stability of bentonite, improves the rheology performance and well wall stability of drilling fluid, and is suitable for deep formation oil and gas mining.
Smart Images

Figure CN119569945A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemical industry, and in particular to a five-component random copolymer and a preparation method thereof, a fluid loss reducer and a water-based drilling fluid. Background Art
[0002] With the development of economy, people's demand for oil and gas resources has become more urgent. Oil and gas exploration has been developing to deeper strata, and the formation conditions that need to be overcome are becoming more and more harsh. Drilling fluid plays a very critical role in ensuring the safety and rapid drilling of deep and ultra-deep wells. However, due to the significant changes in the rheological properties and filtration properties of drilling fluids under high temperature and high salt conditions, the mud cake will be drastically thickened, the permeability will increase, and the stability of the wellbore will also be greatly affected. Therefore, the development of high temperature and salt resistant filtration reducers for drilling fluids is one of the challenges facing deep and ultra-deep well drilling fluids.
[0003] Traditional fluid loss reducers are mainly lignite, modified lignin, resin, etc. Although they are widely available and cheap, they have viscosity loss under high temperature and high pressure conditions, resulting in poor rheological properties of drilling fluids, easy decomposition at high formation temperatures, and easy to be oxidized by Ca. 2+ Mg 2+ Problems such as pollution have caused complex underground conditions and limited its practical application.
[0004] At present, acrylamide-based fluid loss reducers have unsatisfactory fluid loss reduction performance under high temperature conditions because the polymer molecular chains are easily degraded at high temperatures and the desorption problem is serious. Their temperature and salt resistance still cannot meet the actual needs of deep well and ultra-deep well drilling fluids. Therefore, it is very urgent to develop new polymer fluid loss reducers with better performance. Summary of the invention
[0005] In order to solve the above problems, the purpose of the present invention is to provide a five-component random copolymer and its preparation method, a fluid loss reducer and a water-based drilling fluid. As a fluid loss reducer, the five-component random copolymer has the characteristics of high temperature resistance and salt resistance, and has a lower fluid loss in fresh water slurry or salt water.
[0006] In order to achieve the above-mentioned object, the present invention provides a five-membered random copolymer, which is formed by free radical copolymerization of 2-acrylamide-2-methyl-1-propane sulfonic acid, N-alkenylamide, dimethyldiallylammonium chloride, N-vinylcaprolactam and alkenyl heterocyclic compound; the molar ratio of the N-alkenylamide, 2-acrylamide-2-methyl-1-propane sulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam and alkenyl heterocyclic compound is (6-8): (1.7-4): (0.5-2): (1-2): (1-2).
[0007] The side chain of the five-membered random copolymer provided by the present invention has a sulfonic acid group (which can be provided by 2-acrylamide-2 methyl-1-propane sulfonic acid), a quaternary ammonium salt cationic group (which can be provided by dimethyl diallyl ammonium chloride), and a heterocyclic group (which can be provided by an alkenyl heterocyclic compound). The sulfonic acid group on the side chain in the polymer molecule can play a good hydration effect, and is insensitive to cations, has a good salt resistance and enhances the dispersion stability of bentonite; the quaternary ammonium salt cationic group on the side chain can produce a strong adsorption effect with bentonite, which can not only enable the polymer to be adsorbed with bentonite, but also, due to the anti-polyelectrolyte effect, make the polymer chain more stretched, and improve its own salt resistance; the heterocyclic group on the side chain can not only improve the adsorption capacity with bentonite, but also the larger steric hindrance further improves the temperature resistance of the polymer; the N-alkenyl amide monomer has a better ability to resist high temperature degradation relative to amide groups such as acrylamide, and even if it is decomposed, it can produce an amine group to produce an adsorption effect with clay. Therefore, the five-membered random copolymer in the present invention, as a water-based polymer, has the effect of resisting high temperature and high salt, can improve the aggregation state of bentonite, make bentonite have better hydration dispersion stability, and less aggregation of clay particles themselves, so that the formed filter cake is denser and the filtration loss is lower.
[0008] In some specific embodiments, the structure of the above-mentioned five-membered random copolymer can be expressed as follows:
[0009]
[0010] Wherein, R1 is H or an alkyl group with a carbon number of 1-8, R2 is H or an alkyl group with a carbon number of 1-8, and R3 is an aromatic heterocycle. m:n:p:q:r can be (6-8):(2 -4):(0.5-2):(1-2):(1-2).
[0011] In the structure of the five-membered random copolymer, the dimethyldiallyl ammonium chloride can form a five-membered structure by cyclopolymerization during the polymerization process. During the polymerization process, the allyl group in the dimethyldiallyl ammonium chloride can undergo chain transfer, and the conversion rate of the monomer and the molecular weight of the five-membered random copolymer can be controlled by controlling the addition amount of the dimethyldiallyl ammonium chloride monomer.
[0012] The N-alkenyl amide monomer used in the present invention has good chemical stability. Even if it degrades at high temperature, it still retains the amine group to produce adsorption force on clay, and can avoid the problem that traditional acrylamide and N-substituted alkanes are hydrolyzed into carboxylic acids at high temperature, resulting in polymer precipitation and condensation, thereby affecting their fluid loss reduction performance.
[0013] Specifically, the structural formula of the N-alkenyl amide may be:
[0014]
[0015] Wherein, R1 is H or an alkyl group with a carbon number of 1 to 8, and R2 is H or an alkyl group with a carbon number of 1 to 8. Preferably, R1 is H or a methyl group, and R2 is H or a methyl group.
[0016] In the above-mentioned pentyl random copolymer, the N-vinyl amide includes one or a combination of two or more of N-vinyl formamide (CAS: 13162-05-5), N-vinylacetamide, and N-methyl-N-vinylacetamide.
[0017] The large rigid ring structure in the alkenyl heterocyclic compound monomer used in the present invention improves the temperature resistance of the polymer molecular chain, and the nitrogen-containing heterocycle can enhance the adsorption interaction between the polymer and the clay, thereby effectively forming a hydration layer on the clay surface, so that the clay particles themselves have good dispersion stability and show low filtration loss in both fresh water and salt water.
[0018] In the above-mentioned five-membered random copolymer, the alkenyl heterocyclic compound includes one or a combination of two or more of N-vinylimidazole, vinylpyridine, N-vinylcarbazole, and 4-methyl-5-vinylthiazole, for example, a combination of vinylimidazole and vinylcaprolactam. In some specific embodiments, the alkenyl heterocyclic compound may include one or a combination of two or more of N-vinylimidazole, N-vinylcarbazole, and vinylpyridine.
[0019] The structural formula of N-vinyl imidazole is:
[0020] The structural formula of vinyl pyridine is:
[0021] The structural formula of N-vinyl carbazole is:
[0022] The structural formula of 4-methyl-5-vinylthiazole is:
[0023] In the above-mentioned five-membered random copolymer, the molar ratio of the N-alkenyl amide, 2-acrylamido-2-methyl-1-propane sulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam and alkenyl heterocyclic compound is (6-8): (1.7-4): (0.5-2): (1-2): (1-2), and can further be (6-8): (2-4): (0.5-2): (1-2): (1-2). The present invention controls the ratio between N-alkenyl amide, 2-acrylamide-2-methyl-1-propane sulfonic acid, dimethyl diallyl ammonium chloride, N-vinyl caprolactam and alkenyl heterocyclic compounds, on the one hand, can ensure a high monomer conversion rate (up to 95% or more) in the process of synthesizing the five-membered random copolymer, so that the monomers react fully, the initial monomer molar ratio of the feed is guaranteed, and then a five-membered random copolymer with a higher molecular weight is obtained; on the other hand, the drilling fluid prepared from the five-membered random copolymer obtained within the above ratio range has good performance indicators, and the functions of each monomer can be fully exerted. In some specific embodiments, the five-membered random copolymer can be formed by free radical copolymerization of one of N-vinyl imidazole, N-vinyl carbazole, and vinyl pyridine with 2-acrylamide-2-methyl-1-propane sulfonic acid, N-methyl-N-vinylacetamide, dimethyl diallyl ammonium chloride, and N-vinyl caprolactam.
[0024] In some specific embodiments, in the above monomers, the N-alkenyl amide may be 6-8 parts by mole, for example, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, and the like, and a range with any two of the above specific values as endpoints;
[0025] The 2-acrylamido-2-methyl-1-propane sulfonic acid may be 1.7-4 parts, for example, 1.7 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, and other specific values, as well as a range with any two of the above specific values as endpoints;
[0026] The dimethyldiallylammonium chloride may be 0.5-2 parts, for example, 0.5-1 parts, or specific values such as 0.5 parts, 1 parts, 1.5 parts, 2 parts, and a range with any two of the above specific values as endpoints;
[0027] The N-vinyl caprolactam may be 1-2 parts, for example, 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, and other specific values, as well as ranges with any two of the above specific values as endpoints;
[0028] The alkenyl heterocyclic compound can be 1-2 parts, for example, 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts and other specific values, as well as ranges with any two of the above specific values as endpoints.
[0029] In the above-mentioned five-membered random copolymer, the weight average molecular weight of the five-membered random copolymer is 247kDa-366kDa. In some specific embodiments, the weight average molecular weight of the five-membered random copolymer can be 247kDa, 250kDa, 260kDa, 270kDa, 280kDa, 290kDa, 300kDa, 310kDa, 320kDa, 330kDa, 340kDa, 350kDa, 360kDa, 366kDa and other specific values and the range with any two of the above specific values as endpoints.
[0030] The present invention also provides a method for preparing the above-mentioned five-membered random copolymer, comprising:
[0031] The monomers are mixed with water to form a reaction solution, and an initiator is added in an oxygen-free protective atmosphere to carry out a free radical copolymerization reaction to obtain a five-membered random copolymer;
[0032] The monomers include N-alkenylamide, 2-acrylamido-2-methyl-1-propanesulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam and alkenyl heterocyclic compounds;
[0033] The free radical copolymerization reaction temperature is greater than 70° C. and less than or equal to 90° C., and the free radical copolymerization reaction time is 2-10 hours.
[0034] In some specific embodiments, the preparation method may adopt a solution polymerization method. The mass of the monomer may be 20%-40% of the mass of the reaction solution.
[0035] In the above preparation method, the initiator may include one of potassium persulfate, ammonium persulfate, ammonium persulfate / sodium bisulfite, azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutylimidazoline hydrochloride, and 2,2-azobis(2-methylpropionamidine) hydrochloride. In some specific embodiments, the initiator may include azobisisobutyronitrile or azobisisobutylimidazoline hydrochloride.
[0036] In the above preparation method, the mass of the initiator is generally controlled to be 0.1%-1% of the total mass of the monomers. Specifically, the mass of the initiator can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 1.0% and other specific values of the total mass of the monomers, as well as a range with any two of the above specific values as endpoints. In some specific embodiments, the mass of the initiator can be 0.7%-0.85%.
[0037] In the above preparation method, the pH value of the reaction solution is 6 to 9. In some specific embodiments, the pH value of the reaction solution can be adjusted with an acid-base regulator such as sodium hydroxide.
[0038] In the above preparation method, all monomers may be added at the same time, and then the pH value of the system may be adjusted; or a portion of the monomers may be added first, and then the remaining monomers may be added after the pH value is adjusted. The present invention has no particular limitation on the order of adding monomers and adjusting the pH value, as long as the pH value of the reaction system is kept consistent.
[0039] In the above preparation method, the temperature of the free radical copolymerization reaction is generally greater than 70°C and less than or equal to 90°C, for example, greater than 70°C and less than or equal to 75°C, 75°C-90°C, etc. Specifically, the reaction temperature can be 70.1°C, 71°C, 72°C, 73°C, 74°C, 75°C, 80°C, 85°C, 90°C, etc., and a range with any two of the above specific values as endpoints.
[0040] In the above preparation method, the free radical copolymerization reaction time is generally 2h-10h, for example 6h-8h. Specifically, the reaction time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and other specific values, as well as a range with any two of the above specific values as endpoints.
[0041] According to a specific embodiment of the present invention, the preparation method of the above-mentioned five-membered random copolymer may specifically include:
[0042] N-alkenyl amide, 2-acrylamido-2-methyl-1-propane sulfonic acid, dimethyldiallylammonium chloride, N-vinyl caprolactam and alkenyl heterocyclic compounds as monomers are mixed in a molar ratio of (6-8):(2-4):(0.5-2):(1-2):(1-2) to form a reaction solution; in an oxygen-free protective atmosphere, an initiator is added to the reaction solution to carry out a free radical copolymerization reaction at a temperature greater than 70° C. and less than or equal to 90° C. for a reaction time of 2 h to 10 h to obtain a five-membered random copolymer.
[0043] In some specific embodiments, the oxygen-free protective atmosphere comprises nitrogen and / or argon.
[0044] The present invention also provides a fluid loss reducer, which includes the above-mentioned five-membered random copolymer or is made of the above-mentioned five-membered random copolymer. The fluid loss reducer made of the five-membered random copolymer provided by the present invention has the ability to resist high temperature (tolerance to high temperature of 200°C) and salt, and can improve the density of the filter cake and reduce the fluid loss, and is a new type of high temperature and salt resistant polymer fluid loss reducer.
[0045] The present invention also provides a water-based drilling fluid, which includes the above-mentioned fluid loss reducer. The five-membered random copolymer in the above-mentioned fluid loss reducer has a strong adsorption effect on clay and other components in the drilling fluid, can improve the aggregation state and hydration dispersion stability of the clay, and reduce the fluid loss. In some specific embodiments, the water-based drilling fluid includes clay, and the clay can be bentonite, such as sodium bentonite.
[0046] The beneficial effects of the present invention include:
[0047] 1. The present invention adopts N-vinylamide monomer to synthesize the five-membered random copolymer, and can utilize the good chemical stability of N-vinylamide monomer, so that the five-membered random copolymer can still retain the amine group to produce adsorption force on clay such as bentonite even if it degrades at high temperature, and avoids the problem that traditional acrylamide and N-substituted alkanes are hydrolyzed into carboxylic acids at high temperature, resulting in polymer precipitation and condensation, thereby affecting its fluid loss reduction performance.
[0048] 2. The present invention uses alkenyl heterocyclic compound monomers to synthesize a five-membered random copolymer, and can utilize the large rigid ring structure in the alkenyl heterocyclic compound to improve the temperature resistance of the polymer molecular chain. At the same time, the nitrogen-containing heterocycle can enhance the adsorption interaction between the polymer and the clay, thereby effectively forming a hydration layer on the clay surface, so that the clay particles themselves have good dispersion stability and show low filtration loss in both fresh water and salt water.
[0049] 3. The five-membered random copolymer provided by the present invention can be used as a high temperature and salt resistance fluid loss reducer, and still has good fluid loss reduction ability under high temperature and high salt conditions. Specifically, the water-based drilling fluid containing the fluid loss reducer can still maintain a low fluid loss in fresh water slurry and salt water slurry after aging at 200°C for 16 hours, and the fluid loss reduction effect is better than commercial samples such as Driscal D and Dristemp. The fluid loss reducer of the five-membered random copolymer provided by the present invention can be applied to water-based drilling fluid, and is suitable for deep formation oil and gas production construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The pentad random copolymer of Example 1 and its raw material monomers are shown in Figure 1.
[0051] Figure 2The hydrogen NMR spectra of the five-membered random copolymers of Examples 1 to 5 are shown in FIG.
[0052] Figure 3 The hydrogen nuclear magnetic spectra of the copolymers of Comparative Examples 1 to 6 are shown in FIG. DETAILED DESCRIPTION
[0053] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0054] In the following examples and comparative examples, the weight average molecular weight and molecular weight distribution of the polymers were measured by gel permeation chromatograph Waters 1525, which was equipped with a CoMetre 6000LDI pump, a Shodex SB-804HQ chromatographic column and a Schambeck SFD GmbH RI2000 differential detector, wherein the polymer sample was prepared into a 2 mg / mL solution.
[0055] In the following examples and comparative examples, the monomer conversion rate is calculated by precipitating the polymer solution obtained by the reaction with acetone, washing the obtained precipitate, and then drying the obtained solid sample. The ratio of the weight of the solid sample to the mass of the monomer in the reaction solution is the monomer conversion rate.
[0056] Example 1
[0057] This embodiment provides a five-membered random copolymer, which is prepared from five raw materials, namely, N-methyl-N-vinylacetamide (VMA), 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS), dimethyldiallylammonium chloride (DMDAAC), N-vinylcaprolactam (NVCL), and N-vinylimidazole (VIM), as well as sodium hydroxide solution and azobisisobutyronitrile. The preparation method is as follows:
[0058] 1. Add 6.21 g of 2-acrylamide-2-methyl-1-propane sulfonic acid to 48 mL of deionized water, adjust the pH to 7 with a 30% NaOH solution, and then transfer to a 250 mL three-necked flask, add 8.91 g of N-methyl-N-vinylacetamide, 2.43 g of dimethyldiallylammonium chloride aqueous solution (the solute mass is 60% of the solution mass), 1.41 g of N-vinylimidazole and 2.1 g of N-vinylcaprolactam, and stir well to obtain a uniform reaction solution.
[0059] 2. Fill the reaction solution with enough nitrogen to exclude oxygen, add a thermometer, heat to 75°C while stirring, then add 157.5 mg of azobisisobutyronitrile, and continue stirring for 6 hours. After the reaction, a light yellow viscous five-membered random copolymer is obtained. After precipitation and washing in an appropriate amount of acetone, it is placed in a vacuum drying oven at 60°C for drying and grinding to obtain the final copolymer product, which can be used as a new type of high temperature and salt resistant polymer filtrate reducer. The polymer weight average molecular weight is 247kDa (GPC, H2O), and the monomer conversion rate is 95.6%.
[0060] Comparison of the H NMR spectra of the polymer and monomer prepared in Example 1 Figure 1 As shown, M1, M2, M3, M4, and M5 correspond to the NMR hydrogen spectra of monomers VMA, AMPS, DMDAAC, NVCL, and VIM, respectively. By comparing the olefin hydrogen peaks of the double bonds of the monomers, it can be seen that the peak at the chemical shift of 5.5 to 6.0 ppm is the olefin hydrogen of the DMDAAC monomer, and the peak at 6.9 to 7.4 ppm is the olefin hydrogen peak of VMA. No olefin hydrogen peak appears in the spectrum of Example 1, indicating that the monomer reaction is complete.
[0061] Example 2
[0062] This embodiment provides a five-membered random copolymer, which is prepared from five raw materials, namely, N-vinyl acetamide (VMA), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS), dimethyl diallyl ammonium chloride (DMDAAC), N-vinyl caprolactam (NVCL), and N-vinylimidazole (VIM), as well as sodium hydroxide solution and azobisisobutyronitrile. The preparation method is as follows:
[0063] 1. Add 6.21 g of 2-acrylamide-2-methyl-1-propane sulfonic acid to 48 mL of deionized water, adjust the pH to 7 with a 30% NaOH solution, and then transfer to a 250 mL three-necked flask, add 11.88 g of N-methyl-N-vinylacetamide, 2.43 g of dimethyldiallylammonium chloride (60% aqueous solution), 1.41 g of N-vinylimidazole and 2.1 g of N-vinylcaprolactam, and stir well to obtain a uniform reaction solution.
[0064] 2. Fill the reaction solution with enough nitrogen to exclude oxygen, heat to 75°C while stirring, then add 180 mg of azobisisobutyronitrile, and continue stirring for 6 hours. After the reaction, a light yellow viscous five-membered random copolymer is obtained. After precipitation and washing in an appropriate amount of acetone, it is placed in a vacuum drying oven at 60°C for drying and grinding to obtain the final copolymer product, which can be used as a new type of high temperature and salt resistant polymer filtrate reducer. The polymer weight average molecular weight is 287 kDa (GPC, H2O), and the monomer conversion rate is about 100%.
[0065] Example 3
[0066] This embodiment provides a five-membered random copolymer, which is prepared from five raw materials, N-methyl-N-vinyl acetamide (VMA), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS), dimethyldiallylammonium chloride (DMDAAC), N-vinyl caprolactam (NVCL), N-vinyl carbazole, sodium hydroxide solution, and azobisisobutyronitrile. The preparation method is as follows:
[0067] 1. Add 12.42 g of 2-acrylamide-2-methyl-1-propane sulfonic acid to 69 mL of deionized water, adjust the pH to 7 with a 30% NaOH solution, and then transfer to a 250 mL three-necked flask, add 8.91 g of N-methyl-N-vinyl acetamide, 2.43 g of dimethyldiallylammonium chloride (60% aqueous solution), 2.89 g of N-vinylcarbazole and 2.1 g of N-vinylcaprolactam, and stir well to obtain a uniform reaction solution.
[0068] 2. Fill the reaction solution with enough nitrogen to exclude oxygen, heat to 75°C while stirring, then add 228 mg of azobisisobutyronitrile, and continue stirring for 6 hours. After the reaction is completed, a light yellow viscous five-membered random copolymer is obtained. After precipitation and washing in an appropriate amount of acetone, it is placed in a vacuum drying oven at 60°C for drying and grinding to obtain the final copolymer product, which can be used as a new type of high temperature and salt resistant polymer filtrate reducer. The weight average molecular weight of this polymer is 366kDa (GPC, H2O), and the monomer conversion rate is about 100%.
[0069] Example 4
[0070] This embodiment provides a five-membered random copolymer, which is prepared from five raw materials, namely, N-methyl-N-vinylacetamide (VMA), 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS), dimethyldiallylammonium chloride (DMDAAC), N-vinylcaprolactam (NVCL), and N-vinylimidazole (VIM), as well as sodium hydroxide solution and azobisisobutyronitrile. The preparation method is as follows:
[0071] 1. Add 12.42 g of 2-acrylamide-2-methyl-1-propane sulfonic acid to 69 mL of deionized water, adjust the pH to 7 with a 30% NaOH solution, and then transfer to a 250 mL three-necked flask, add 11.88 g of N-methyl-N-vinylacetamide, 2.43 g of dimethyldiallylammonium chloride (60% aqueous solution), 1.41 g of N-vinylimidazole and 2.1 g of N-vinylcaprolactam, and stir well to obtain a uniform reaction solution.
[0072] 2. Fill the reaction solution with enough nitrogen to exclude oxygen, add a thermometer, heat to 75°C while stirring, then add 226.8 mg of azobisisobutyronitrile, and continue stirring for 6 hours. After the reaction, a light yellow viscous five-membered random copolymer is obtained. After precipitation and washing in an appropriate amount of acetone, it is placed in a vacuum drying oven at 60°C for drying and grinding to obtain the final copolymer product. The copolymer can be used as a new type of high temperature and salt resistant polymer filter loss reducer. The polymer weight average molecular weight is 352kDa (GPC, H2O), and the monomer conversion rate is about 100%.
[0073] Example 5
[0074] This embodiment provides a five-membered random copolymer, which is prepared from five raw materials, N-methyl-N-vinyl acetamide (VMA), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS), dimethyldiallylammonium chloride (DMDAAC), N-vinyl caprolactam (NVCL), vinyl pyridine, sodium hydroxide solution, and azobisisobutyronitrile. The preparation method is as follows:
[0075] 1. Add 9.33 g of 2-acrylamide-2-methyl-1-propane sulfonic acid to 66 mL of deionized water, adjust the pH to 7 with a 30% NaOH solution, and then transfer to a 250 mL three-necked flask, add 11.88 g of N-methyl-N-vinyl acetamide, 3.66 g of dimethyldiallylammonium chloride (60% aqueous solution), 1.57 g of vinylpyridine and 2.1 g of N-vinylcaprolactam, and stir well to obtain a uniform reaction solution.
[0076] 2. Fill the reaction solution with enough nitrogen to exclude oxygen, add a thermometer, heat to 75°C while stirring, then add 213 mg of azobisisobutyronitrile, and continue stirring for 6 hours. After the reaction, a light yellow viscous five-membered random copolymer is obtained. After precipitation and washing in an appropriate amount of acetone, it is placed in a vacuum drying oven at 60°C for drying and grinding to obtain the final copolymer product. The copolymer can be used as a new type of high temperature and salt resistant polymer filtrate reducer. The polymer weight average molecular weight is 318kDa (GPC, H2O), and the monomer conversion rate is about 99.4%.
[0077] Figure 2 The H NMR spectra of the copolymer products prepared in Examples 1 to 5 are quantitatively analyzed using DMF as an internal standard, indicating that the monomers in Examples 1 to 5 have reacted completely and have high conversion rates.
[0078] Comparative Example 1
[0079] This comparative example provides a method for preparing a polymer, which adopts a precipitation polymerization method, and the specific process is:
[0080] In a 100mL three-necked round-bottom flask, add 47mL of tert-butanol and heat to 40°C. Add AMPS (4.1g, 19.8mmol) to tert-butanol, AMPS is suspended and insoluble; continue to add triethylamine in an equal molar amount to AMPS, AMPS gradually dissolves, and after the solution is clarified, adjust the pH value of the solution to about 8.0 with a 30wt% NaOH aqueous solution. Then add the remaining four monomers according to the monomer molar ratio VMA:AMPS:DMDAAC:NVCL:VIM=6:2:2:1:1, fill with argon to exclude oxygen (30min), and continue to heat to 60°C. Add initiator azobisisobutyronitrile AIBN (the mass of initiator is 0.9% of the total mass of monomers). After continuing to stir and react for 2h, the solution begins to become viscous. Continue to heat to 69°C and react for another 2h. Then, heat to 75°C, react for 2h, and stop the reaction. The crude product of the reaction is a light yellow viscous liquid, which can be washed, dried and ground to obtain the final product.
[0081] Comparative Example 2
[0082] This comparative example provides a method for preparing a polymer, which adopts a solution polymerization method, and the specific process is as follows:
[0083] 4.1g of monomer AMPS was added to a three-necked flask containing 64mL of water to dissolve, and the pH was adjusted to about 8 with a 30wt% NaOH aqueous solution; the remaining four monomers were added according to the monomer molar ratio of VMA:AMPS:DMDAAC:NVCL:VIM=6:2:2:1:1, and the chain transfer agent ethanol (ethanol is about 10% of the water content); argon was filled to exclude oxygen (30min), the temperature was raised to 70°C, and the initiator azobisisobutyronitrile AIBN was added, the mass of the initiator was 0.75% of the total mass of the monomers, and the reaction was continued for 2h to terminate the reaction. After the reaction was completed, the crude reaction product was a light yellow viscous liquid, which was washed, dried, and ground to obtain the final product.
[0084] Comparative Example 3
[0085] This comparative example provides a method for preparing a polymer, which comprises:
[0086] Take 10mL of water and add it to a 100mL three-necked flask, and dissolve the monomer AMPS in a beaker containing 8mL of water, and adjust the pH of the AMPS aqueous solution to about 8 with a 30%wt NaOH aqueous solution; add the remaining four monomers to the beaker according to the monomer molar ratio VMA:AMPS:DMDAAC:NVCL:VIM=6:2:2:1:1; fill with argon to exclude oxygen (30min), raise the temperature in the three-necked flask to 100°C, first add 3mL of the monomer mixed solution, and then slowly add the remaining monomer solution and the initiator azobisisobutylimidazoline hydrochloride VA-044 to the three-necked flask at the same time, add all of them in about 1h, and the mass of the initiator is 1.5% of the total mass of the monomers; continue the reaction for 5h to end the reaction. After the reaction is completed, the crude reaction product is a light yellow viscous liquid, which is washed, dried and ground to obtain the final product.
[0087] Comparative Example 4
[0088] This comparative example provides a method for preparing a polymer, which comprises:
[0089] 2.07g of monomer AMPS was added to a three-necked flask containing 35mL of water to dissolve, and the pH was adjusted to about 8 with a 30wt% NaOH aqueous solution; the remaining four monomers were added according to the monomer molar ratio of VMA:AMPS:DMDAAC:NVCL:VIM=6:2:2:1:1, argon was introduced to exclude oxygen (30min), the temperature was raised to 60°C, the initiator azobisisobutylimidazoline hydrochloride VA-044 was added, the mass of the initiator was 1.5% of the total mass of the monomers, and the reaction was continued for 4h to terminate the reaction. After the reaction was completed, the crude reaction product was a light yellow viscous liquid, which was washed, dried and ground to obtain the final product.
[0090] Comparative Example 5
[0091] This comparative example provides a method for preparing a polymer, which comprises:
[0092] Add 2.07g of AMPS monomer into a three-necked flask containing an appropriate amount of water to dissolve, and adjust the pH to about 8 with a 30wt% NaOH aqueous solution; add the remaining four monomers according to the monomer molar ratio of VMA:AMPS:DMDAAC:NVCL:VIM=6:2:2:1:1; fill with argon to exclude oxygen (30min), raise the temperature to 60°C, add initiator azobisisobutylimidazoline hydrochloride VA-044, the mass of the initiator is 0.75% of the total mass of the monomers, and continue the reaction for 10h to terminate the reaction. After the reaction is completed, the crude reaction product is a light yellow viscous liquid, which is washed, dried, and ground to obtain the final product.
[0093] Comparative Example 6
[0094] This comparative example provides a method for preparing a polymer, which comprises:
[0095] 2.07g of monomer AMPS was added to a three-necked flask containing an appropriate amount of water to dissolve, and the pH was adjusted to about 8 with a 30wt% NaOH aqueous solution; the remaining four monomers were added according to the monomer molar ratio of VMA:AMPS:DMDAAC:NVCL:VIM=6:2:2:1:1; argon was filled to exclude oxygen (30min), the temperature was raised to 50°C, initiator VA-044 was added, the mass of the initiator was 0.75% of the total mass of the monomers, and the reaction was continued for 10h to terminate the reaction. After the reaction was completed, a light yellow viscous liquid was obtained, which was washed, dried and ground to obtain the final product.
[0096] Comparison of the H NMR spectra of the polymers and monomers prepared in Comparative Examples 1 to 6 Figure 3 As shown, there is an obvious monomer olefin hydrogen absorption peak at 5.0-8.0 ppm, and the monomer conversion rate is low.
[0097] The molecular weights and monomer conversion rates of the copolymers of Examples 1 to 5 and the final products of Comparative Examples 1 to 6 are shown in Table 1:
[0098] Table 1
[0099] . Mw / kDa PDI Monomer conversion Comparative Example 1 79 2.122 55.3% Comparative Example 2 178 2.781 64.0% Comparative Example 3 96 2.569 68.5% Comparative Example 4 195 3.141 70.0% Comparative Example 5 319 2.287 77.6% Comparative Example 6 327 2.979 61.3% Example 1 247 3.768 95.6% Example 2 287 3.679 100% Example 3 366 3.528 100% Example 4 352 4.130 100% Example 5 318 4.720 99.4%
[0100] As can be seen from the results in Table 1, compared with precipitation polymerization, the solution polymerization method of the present invention is more conducive to obtaining a higher monomer conversion rate and a copolymer with a higher molecular weight. On this basis, the present invention can further improve the monomer conversion rate of the copolymerization reaction and the molecular weight of the copolymer obtained thereby by controlling parameters such as reaction temperature and initiator dosage.
[0101] Test Example 1
[0102] This test example provides an evaluation of the rheological properties and fluid loss control performance of the waterborne five-membered random copolymer prepared in the above examples.
[0103] 1. Test in freshwater test slurry
[0104] The five-membered random copolymers prepared in Example 1, Example 2, Example 3, Example 4, and Example 5 were evaluated for their temperature resistance and fluid loss reduction performance as fluid loss reducers in bentonite slurry. After aging at 200° C. for 16 h, the pressure loss in each slurry was measured using a Qingdao Tongchun quadruple water loss meter SD4 according to the provisions of GB / T16783.1-2014 Drilling Fluid Field Test. The composition of the evaluation slurry is as follows:
[0105] Freshwater test slurry: 4% bentonite + 2% fluid loss reducer (penta-random copolymer)
[0106] Fresh water-based slurry: Add 400 mL of tap water to a high-stirring cup, add 16 g of bentonite quantitatively while stirring continuously, and stir for 20 minutes, stopping at least twice to scrape off the clay (bentonite) adhering to the container wall, and cure in a sealed container for 24 hours.
[0107] Preparation of polymer drilling fluid system: quantitatively weigh the polymer to be tested, mix and dissolve the polymer with 400 mL of the above-mentioned fresh water base slurry, stir at high speed for 20 minutes, and leave it for 24 hours to obtain a polymer drilling fluid system of a certain concentration (mass volume concentration).
[0108] Table 2 shows the performance test results of the new high temperature and salt resistant polymer fluid loss reducer in fresh water slurry, using the GB / T16783.1-2014 drilling fluid field test procedure. AV is the apparent viscosity, PV is the plastic viscosity, YP is the dynamic shear force, FL is the API It is the medium pressure filtration loss at room temperature.
[0109] Table 2
[0110]
[0111] It can be seen from Table 2 that adding 2% of the prepared fluid loss agent sample to the freshwater test slurry can significantly increase the apparent viscosity and plastic viscosity, and can still maintain a certain viscosity after aging at high temperature of 200°C for 16 hours, indicating that the polymer has a good viscosity-increasing effect and good temperature resistance. The FL after high temperature aging API It can reach 7.2mL, which has a good effect of reducing filtration loss.
[0112] 2. Test in salt water test slurry
[0113] Comparative sample 1 is a temperature-resistant polymer fluid loss reducer, Driscal D, from Chevron Phillips Chemical Company LP Drilling Specialties Company LLC;
[0114] Comparative sample 2 is Dristemp, a temperature-resistant polymer fluid loss reducer produced by Chevron Phillips Chemical Company LP Drilling Specialties Company LLC.
[0115] The temperature resistance and fluid loss reduction performance of the fluid loss reducers of Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Sample 1 and Comparative Sample 2 in bentonite slurry were evaluated. After aging at 200°C for 16 hours, the pressure loss in each slurry was measured using Qingdao Tongchun Quadruple Loss Meter SD4 according to the provisions of "GB / T16783.1-2014 Drilling Fluid Field Test". The composition of the evaluation slurry is as follows:
[0116] Salt water test slurry: 4% bentonite + 2% fluid loss reducer + 15% NaCl
[0117] Fresh water-based slurry: Add 400 mL of tap water to a high-stirring cup, add 16 g of bentonite quantitatively while stirring continuously, and stir for 20 minutes, stopping at least twice to scrape off the clay (bentonite) adhering to the container wall, and cure in a sealed container for 24 hours.
[0118] Preparation of salt water slurry of polymer drilling fluid system: quantitatively weigh the prepared polymer, mix and dissolve the polymer with 400 mL of the above-mentioned fresh water base slurry, add 15% NaCl, stir at high speed for 20 minutes, and leave for 24 hours to obtain a polymer salt water slurry drilling fluid system of a certain concentration (mass volume concentration).
[0119] The evaluation results are shown in Table 3. The GB / T16783.1-2014 drilling fluid field test procedure was used.
[0120] Table 3 shows the performance test results of the new high temperature and salt resistant polymer fluid loss reducer and the comparative samples in salt water slurry. AV is the apparent viscosity, PV is the plastic viscosity, YP is the dynamic shear force, FL is the API -API is the filtration loss.
[0121] Table 3
[0122]
[0123]
[0124] The test results in Table 3 show that compared with Comparative Samples 1 and 2, the salt water test slurry prepared with the high temperature and salt water resistant polymer of the present invention has better filtration loss reduction performance. After hot rolling aging at 200°C for 16 hours, the medium pressure filtration loss at room temperature is as low as 9.0 mL, which has better heat and salt resistance than Driscal D and Dristemp. The high temperature and salt water resistant polymer of the present invention has a lower molecular weight, and the rheological parameters such as apparent viscosity, plastic viscosity, and dynamic shear force of the prepared fresh water and salt water test slurries have lower values. The rheological parameters change less before and after hot rolling aging at 200°C for 16 hours, and the high temperature stability is better.
[0125] The above test results show that the high temperature and salt water resistant polymer of this embodiment has good rheological properties and filtration reduction effect in fresh water and saturated 15% salt water drilling fluid. The performance remains stable after hot rolling at 200°C for 16 hours, which is significantly better than similar filtration reducer products.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A five-membered random copolymer, which is formed by free radical copolymerization of 2-acrylamido-2-methyl-1-propane sulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam, N-alkenylamide and alkenyl heterocyclic compound; The molar ratio of the N-alkenyl amide, 2-acrylamido-2-methyl-1-propane sulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam and the alkenyl heterocyclic compound is (6-8): (1.7-4): (0.5-2): (1-2): (1-2).
2. The five-membered random copolymer according to claim 1, wherein The N-alkenyl amide includes one or a combination of two or more of N-vinyl formamide, N-vinylacetamide, and N-methyl-N-vinylacetamide.
3. The five-membered random copolymer according to claim 1, wherein The alkenyl heterocyclic compound includes one or a combination of two or more of N-vinyl imidazole, vinyl pyridine, N-vinyl carbazole, and 4-methyl-5-vinyl thiazole.
4. The five-membered random copolymer according to claim 1, wherein Preferably, the molar ratio of the N-alkenyl amide, 2-acrylamido-2-methyl-1-propane sulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam and the alkenyl heterocyclic compound is (6-8):(2-4):(0.5-2):(1-2):(1-2).
5. The five-membered random copolymer according to claim 1, wherein The weight average molecular weight of the five-membered random copolymer is 247 kDa-366 kDa.
6. A method for preparing a five-membered random copolymer according to any one of claims 1 to 5, comprising: The monomers are mixed with water to form a reaction solution, and an initiator is added in an oxygen-free protective atmosphere to carry out a free radical copolymerization reaction to obtain a five-membered random copolymer; The monomers include N-alkenylamide, 2-acrylamido-2-methyl-1-propanesulfonic acid, dimethyldiallylammonium chloride, N-vinylcaprolactam and alkenyl heterocyclic compounds; The free radical copolymerization reaction temperature is greater than 70° C. and less than or equal to 90° C., and the free radical copolymerization reaction time is 2-10 hours.
7. The preparation method according to claim 6, wherein: The free radical copolymerization reaction temperature is 75°C-90°C.
8. The preparation method according to claim 6, wherein: The initiator includes one of potassium persulfate, ammonium persulfate, a combination of ammonium persulfate and sodium bisulfite, azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutylimidazoline hydrochloride, and 2,2-azobis(2-methylpropionamidine) hydrochloride; Preferably, the initiator comprises azobisisobutyronitrile or azobisisobutylimidazoline hydrochloride.
9. The preparation method according to claim 6, wherein: The mass of the initiator is 0.1%-1% of the total mass of the monomers.
10. The preparation method according to claim 6, wherein: The pH value of the reaction solution is 6-9.
11. A fluid loss control agent, comprising the five-membered random copolymer according to any one of claims 1 to 5 or made from the five-membered random copolymer according to any one of claims 1 to 5.
12. A water-based drilling fluid comprising the fluid loss reducer according to claim 11.
Citation Information
Patent Citations
Copolymer fluid loss agent with resistance against temperature and salt for drilling liquid and preparation method thereof
CN102453470A
Ultrahigh-temperature-resistant and complex-salt-resistant amphoteric ion hydrophobic association polymer filter loss reducer and preparation method thereof
CN108715624A
Hydrogels Based on Vinyl-Caprolactam
US20210017316A1
Water soluble copolymers containing vinyl imidazole as drilling fluid additives
US4471097A